A német nyelv státuszának változása az oktatásban és az erősítése mellett szóló érvek - Szilvási-Bódis, Zsuzsanna (Acta Carolus Robertus, 2023)
In my study, I present the development of the situation of the German language in the education in our country. I will focus on the changes that have taken place in recent decades, but before all that, I will also briefly talk about the typical status of Germany in historical times. I review the changes according to the place occupied by the language in education, I examine the proportion of students at different educational levels who learn German compared to English and other foreign languages. Looking at the statistical data of the selected years, it is also possible to show the trend in the development of the situation of the individual taught foreign languages. I will also go over why the German language should be given a more important place and role in Hungarian educational institutions, even taking into account the characteristics of each region. Last but not least, I would like to draw attention to the incentive programs that help to learn and preserve the language.